2020
DOI: 10.1093/ndt/gfaa191
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine and azithromycin tolerance in haemodialysis patients during COVID-19 infection

Abstract: Background Haemodialysis patients are at risk of developing severe forms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection: coronavirus disease 2019 (COVID-19). In March 2020, hydroxychloroquine (HCQ) and azithromycin (AZI) were proposed as potential treatments of COVID-19, but with warnings concerning their possible toxicity. No data are available regarding the toxicity of this treatment in haemodialysis patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Hydroxychloroquine was also found safe in a French series of 21 hemodialysis patients [34]. In our extremely ill patients admitted to the ICU, antiviral treatment did not show any bene t regarding mortality but we cannot make further conclusions because it was prescribed in severe cases, which is considered as a bias of indication.…”
Section: Discussionmentioning
confidence: 64%
“…Hydroxychloroquine was also found safe in a French series of 21 hemodialysis patients [34]. In our extremely ill patients admitted to the ICU, antiviral treatment did not show any bene t regarding mortality but we cannot make further conclusions because it was prescribed in severe cases, which is considered as a bias of indication.…”
Section: Discussionmentioning
confidence: 64%
“…Finally, the treatment used in the first diagnosed patients was hydroxychloroquine and did not cause an increase in death as opposed to the study published by the Spanish kidney registry in March 2020 [ 22 ]. Hydroxychloroquine was also found safe in a French series of 21 hemodialysis patients [ 34 ]. In our extremely ill patients admitted to the ICU, antiviral treatment did not show any benefit regarding mortality but we cannot make further conclusions because it was prescribed in severe cases, which is considered as a bias of indication.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the respondents in this study were middle-aged and had undergone hemodialysis for more than 6 months. Several studies have also found the same patient profiles [9], [14], [15], [16] Patients who have been on hemodialysis for a long time tend to be more disciplined in observing therapy schedule despite facing obstacles because they feel the benefits of undergoing therapy [17].…”
Section: Discussionmentioning
confidence: 91%
“…The previous studies on the effects of COVID-19 in hemodialysis patients have focused more on the characteristics of hemodialysis patients suffering from COVID-19 [3], [6], [7], [8], impact of drug trials on hemodialysis patients suffering from COVID-19 [9], and case report of hemodialysis patients with COVID-19 [10], [11]. No study examined hemodialysis adequacy, IDWG, and the quality of life of hemodialysis patients during the pandemic.…”
Section: Introductionmentioning
confidence: 99%